Polska rodzina na progu trzeciego tysiaclecia - Ryszka, Rafal (Lublin : Norbertinum, 2000)
A study of the status of the family in Polish life at the beginning of the third millennium.
Includes bibliographical references.
Keywords: Families -- Poland -- Congresses; Families -- Religious aspects -- Catholic Church -- Congresses